Automotive Battery Technology - Thaler, Alexander; Watzenig, Daniel (Automotive Engineering : Simulation and Validation Methods, Automotive Engineering : Simulation and Validation Methods, 2014)
The use of electrochemical energy storage systems in automotive applications also involves new requirements for modeling these systems, especially in terms of model depth and model quality. Currently, mainly simple application-oriented models are used to describe the physical behavior of batteries. This book provides a step beyond of state-of-the-art modeling showing various different approaches covering following aspects: system safety, misuse behavior (crash, thermal runaway), battery state estimation and electrochemical modeling with the needed analysis (pre/post mortem). All this different approaches are developed to support the overall integration process from a multidisciplinary point-of-view and depict their further enhancements to this process.